Cu2Se thermoelectrics: property, methodology, and device - Liu, Wei-Di; Yang, Lei; Chen, Zhi-Gang (Nano today, 2020)
[Display omitted] •Systematic summary of the fundamentals of Cu2Se-based thermoelectrics.•Detailed summary of thermoelectric performance engineering strategies related with Cu2Se.•Review on the chemical stability, oxidization, mechanical property and devices of Cu2Se.•Point out future research direction of Cu2Se-based thermoelectrics. In the last decade, high-performance Cu2Se thermoelectric materials and devices are attracting increasing research interest. In this review, we firstly summarize fundamentals of Cu2Se, including crystal structure, band structure, phase transition, and intrinsic thermoelectric performance. Then, we compare and overview the effectiveness of enhancing electrical transports and reducing lattice thermal conductivity on boosting figure of merit, zT of Cu2Se and found that zT enhancement of Cu2Se should be mainly attributed to reduced lattice thermal conductivity. After that, we highlight the chemical stability and mechanical properties of Cu2Se and its thermoelectric modules. In the end, we point out future research directions in the field of Cu2Se thermoelectrics. This review fills the gap of overview on the progress and challenge of Cu2Se thermoelectrics, and provide a new perspective to achieve Cu2Se-based thermoelectric materials with high thermoelectric performance.